2019
DOI: 10.1002/pbc.27598
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of bronchoalveolar lavage and respiratory tract biopsies in the diagnosis and management of suspected invasive fungal infection in children with cancer or who have undergone stem cell transplant

Abstract: Background Identification of an organism is the gold standard for the diagnosis of fungal infection; however, we have previously shown that invasive procedures infrequently lead to a change in management in children with cancer or who have undergone stem cell transplant with suspected respiratory tract invasive fungal infection (RT‐IFI). There is also a paucity of data on the cost of RT‐IFI in this population. We therefore compared the costs of RT‐IFI diagnosed based on CT scan alone versus those who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…It indicated that when routine microbiological tests are adverse and empirical treatment is ineffective, BALF mNGS is undoubtedly a valuable pathogen detection tool. Although the utility of bronchoscopy for children remains to be questioned ( Rossoff et al., 2019 ), this procedure positively impacts the pathogenic diagnosis and a subsequent management adjustment of pulmonary infections in this population ( Wohlfarth et al., 2018 ; Bauer et al., 2019 ). Bronchoalveolar lavage (BAL) is usually more feasible and safer than biopsy ( Rao et al., 2013 ; Chellapandian et al., 2015 ; Elbahlawan et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…It indicated that when routine microbiological tests are adverse and empirical treatment is ineffective, BALF mNGS is undoubtedly a valuable pathogen detection tool. Although the utility of bronchoscopy for children remains to be questioned ( Rossoff et al., 2019 ), this procedure positively impacts the pathogenic diagnosis and a subsequent management adjustment of pulmonary infections in this population ( Wohlfarth et al., 2018 ; Bauer et al., 2019 ). Bronchoalveolar lavage (BAL) is usually more feasible and safer than biopsy ( Rao et al., 2013 ; Chellapandian et al., 2015 ; Elbahlawan et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…After the initial decision regarding the use of empiric therapy, the diagnostic tests are ordered. The diagnostic tests incorporated into the model are based on the published estimates by Barnes et al and Rossoff et al as shown in Table 2 [ 4 , 34 ]. The same diagnostic tests were used for both the SoC arm and the Karius Test arm, with the exception of a reduction in bronchoscopy and bronchoalveolar lavage.…”
Section: Methodsmentioning
confidence: 99%
“… Source: Barnes et al and Rossoff et al [ 4 , 34 ] CT computed tomography, PCR polymerase chain reaction, PET positron emission tomography, SoC standard of care …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations